Transportation-oriented spatial allocation of land use development: a simulation-based optimization method. (July 2020) - Lin, Hongzhi; Zhang, Yongping
Urban development usually deteriorates the transportation system. For sustainable urban development, policymakers often face the challenging problem of how to optimally allocate overall land use quotas across a number of residential locations according to the performance of the transportation system. This is a kind of Stackelberg competition, where policymakers make land use decisions and travelers make behavioral responses. A novel bi-level model is formulated to solve this problem. The upper-level model minimizes the total system travel time by land use allocation, while at the lower level are sequential models with feedback for transportation system equilibrium. The Dirichlet allocation algorithm, a simulation-based heuristic algorithm, is designed to solve this bi-level model. A simulation experiment using the Nguyen–Dupuis network is then used to verify the proposed model and algorithm. The results from the simulation experiment demonstrate that not only are the model and algorithm operational but that they also provide an effective tool for policymakers to plan for land use development.